THE EMERGING ROLE OF ACADEMIC DEANS IN THE TRANSFORMING HIGHER EDUCATION LANDSCAPE OF KAZAKHSTAN - Mustafina, Altynay (Nazarbayev University Graduate School of Education, 2024)
Within Kazakhstan’s fast-changing higher education landscape, the nature of academic deanship is also rapidly changing (Arntzen, 2016; Wepner et al., 2015). While deanship has traditionally been associated with curriculum design, student admissions, and faculty hiring, it now also requires engagement in strategic planning, human resource management, budgetary issues, fundraising, and communication with business and industry (Cleverley-Thompson, 2016; Gmelch et al., 2012). Thus, the role of the dean has become a more complex and multifaceted position in academia. Therefore, this study aimed to explore academic deanship in Kazakhstani public universities to find out how deans perceive and experience their jobs, what roles they play as school administrators, and what challenges they face in their positions. For this purpose, this study employed semi-structured in-depth interviews conducted with 15 academic deans from seven public universities (national and regional universities) in Kazakhstan. The study’s findings indicate that the dean’s executive behavior in public universities is rule-bound and context-dependent due to the inherited centralized governance system in Kazakhstan as a post-Soviet republic. These factors explain top-down control, tight control, hierarchical relationships, and centralized decision-making in universities. Under these conditions, the dean’s autonomy in managing academic schools are restricted in the issues associated with finances, decision-making, and problem solving (Hartley et al., 2016; Sagintayeva et al., 2017; Yembergenova et al., 2021). This suggests that deans who are selected as administrators are limited to fully carry out their administrative and managerial functions. These discrepancies in which deans operate explain their role conflict and role ambiguity in the workplace. These findings contribute to the understanding of academic deanship in the context of the post-Soviet higher education system, highlighting that the dean’s managerial potential remains unrecognized (Cleverley-Thompson, 2016; Wepner et al., 2015). Therefore, the practical implications emphasize the need for empowering deans in Kazakhstani public universities by delegating them greater authority. This will strengthen grassroots leadership among deans, enhancing their administrative-managerial status. Regarding the theoretical implications, executive behavioral theory showed that the dean’s managerial behavior is prone to norm-following behavior, suggesting that this theory is more suitable for analyzing decentralized university governance systems. Role conflict and ambiguity theory allowed to examining the dean’s roles from different perspectives, such as individual and institutional levels, offering deeper insights into understanding the phenomenon under study.
Keywords: Type of access: Open Access; academic deanship; Kazakhstan; managerial roles; role conflict; role ambiguity